The fruits of Bakoa nakamotoi - Boyce, P.C; Wong Sin, Yeng (International Aroid Society Inc., 2012)
The infructescences and fruits of Bakoa nakamotoi S.Y. Wong are described and illustrated for the first time. The fruits are shown to be dehiscent berries, the first such recorded example for the Araceae.